How fat will it make me? Estimation of weight gain in anorexia nervosa. (1st July 2017) - Milos, Gabriella; Baur, Volker; Schumacher, Sonja; Kuenzli, Cornelia; Schnyder, Ulrich; Mueller-Pfeiffer, Christoph; Martin-Soelch, Chantal
Abstract: This study investigates the subjective estimation of weight gain in patients with anorexia nervosa (AN) when being confronted with food cues both in a general (self-unrelated) and in an intent-to-eat (self-related) condition. Looking at the presentation of different snack pictures with different nutrition values (high-low calories), AN patients (N = 24) and age-matched healthy women (N = 27) estimated the weight gain when they imagined eating the presented portions of snack pictures once a day in addition to the normal daily nutrition in the following two conditions: 1) a general condition without specific additional instruction, 2) an intent-to-eat condition, in which they were instructed to imagine that they would eat the snack themselves. Compared to healthy women, patients with AN estimated a higher weight gain only in the intent-to-eat condition, i.e. when they imagined eating the snacks themselves, but not in the general, not self-related condition. In the patient group, mean estimations of weight gain were associated with the "drive for thinness". This study suggests cognitive abnormalities related to the effects of food intake on the weight gain in AN, and that these cognitive anomalies could be related to the fear of gaining weight, one central symptom of AN. It appears that the self-reflective disturbed cognition, rather than the general cognition, could be the main driver underlying anorexia and that the overestimation of the energetic content of food is related to the drive for thinness.